Development of the Emirati Child Adaptation Scale (ECAS) for Assessing the Behavioral Adaptation Skills of Children with and without Disabilities in the UAE - Ousha AlMuhairy; Efthymia Efthymiou; Hala ElHoweris; Mahmoud Alshathly; Abdelaziz Sartawi (MDPI AG, 2023)
Behavioral problems cause limitations in the social skills of children without disabilities and affect the functionality of children with disabilities. The Emirati child adaptation scale (ECAS) was developed in the UAE to provide reliable and valid information on the behavioral adaptation skills in children with and without intellectual disability (ID). The scale's item pool consists of 651 items that identify behavioral adaptation deficits across the 10 domain-skill areas of communication, pre-academic, listening, social, self-care, self-orientation, motor skills, operational society, life, and health and safety. The scale was administered to 1542 children with disabilities and 920 children without disabilities. The scale is deemed essential, as it enables psychologists, special education teachers, health professionals, and researchers to implement a reliable psychometric tool of adaptive and behavioral functioning of 1-18-year-old individuals. The development and structure of the Emirati child adaptation scale is described and discussed.